Financiamento de residências, frente ao déficit habitacional brasileiro: contribuição do programa minha casa minha vida - Queiroz, José Rodolpho Régis (2017)
The development process, in accordance with the evolution of its conception, deserves to be understood as the guarantee of well-being, besides the quality of human life. Thus, it distances itself from a purely economic connotation - which confused it with economic growth - and goes on to emphasize the importance of a properly social content. With this in mind, the mechanisms that have the potential to contribute to this development phenomenon are valuable, and access to decent housing is one of them. The guarantee of housing adequate to the satisfactory survival of man represents not only a fundamental right which is in itself already very valuable, but rather denotes the possibility of realizing a series of other fundamental freedoms, quickly exemplified For the right to food, work and leisure. However, although such considerations presuppose the importance of its broad implementation, a special focus on the Brazilian housing panorama allows the conclusion that a series of obstacles are imposed to the realization of this social right, which proves to be a potential contribution of Development of the national population. In order, therefore, to consider the conditions that imply in the ineffectiveness of the focused fundamental freedom, it is worth emphasizing the rigor of the Brazilian real estate market, making the less favored layers economically do not have enough resources to have access to decent housing. In this context, the present research demonstrates the importance of state intervention in the housing sector, presenting as a way of minimizing the obstacles that exclude a significant portion of the Brazilian population from the housing sector, notably through public policies that allow the financing of residences. In view of this, the general objective of this paper is to analyze whether state action through housing finance has the potential to combat the Brazilian housing deficit. Meanwhile, its specific objectives are four: to identify the Brazilian housing deficit as a problem that provokes state intervention; To analyze, through the history of public housing policies already developed in Brazil, whether the Minha Casa Minha Vida Program is adequate to address the problems identified in the country's housing sector; Demonstrate the importance of state financing of housing to reduce the housing deficit; And analyze the structure of the My Home My Life Program and its efficiency in combating the Brazilian housing deficit. In this way, the research problem is represented by the following question: "Housing finance policies, as part of the Minha Casa Minha Vida Program, are effective in combating the Brazilian housing deficit?", Which would be answered by the following hypothesis: "the Combat the problems identified in the Brazilian housing sector demand state intervention, and the My Home My Life Program is effective in this process. " With regard to the methodological procedures used, a technical bibliographical procedure was developed, using the indirect research technique and using the formative reading to analyze data. In view of this, it was concluded by ratification of the hypothesis proposed, and state intervention is recognized as an effective instrument for broad access to housing.